Formação de leitores à luz dos multiletramentos na educação profissional e tecnológica do Instituto Federal de Educação, Ciências e Tecnologia do Acre - Aragão, Maria do Socorro Sousa (2023)
The study deals with reading and reader formation in the light of multiliteracies and, as a delimitation, proposes activities based on reading skills in multimodal texts, with emphasis on the infographic. Therefore, the objective is to develop reading skills from the perspective of multiliteracies of students of the Technical Course Integrated to High School in Professional Technological Education at the Federal Institute of Education, Science and Technology of Acre (Ifac), Campus Rio Branco. In this sense, the research is based on normative documents, highlighting the National Curricular Parameters (1998), the National Common Curricular Base (2018) and the Acre Reference Curriculum for High School (2021). The theoretical support of the work is based on Kleiman (2016a, 2016b) and Santaella (2013), as well as on Bakhtin (2014, 2016), about the discourse genre, on Soares (2009) and Rojo (2009), regarding to literacy, in The New London Group (1996) and Cope and Kalantzis (2000), on multiliteracies, and also in Kanno (2018) to strengthen the multimodal infographic genre, among others. This investigation presents an analysis of an applied nature, with an exploratory character and a quali-quanti approach. Regarding the procedures, it is bibliographical and documental. Data were collected through an initial questionnaire, three pedagogical workshops and the analysis of a final questionnaire, both materialities structure the theme through action research and observation. The results point to a convergence for the proposed objectives, revealing that the infographic as a multimodal text generates reading skills in students, conditioning them to the formation of proficient readers and making them protagonists of a social practice